Whole-exome sequencing in patients with maturation arrest: a potential additional diagnostic tool for prevention of recurrent negative testicular sperm extraction outcomes. Issue 6 (12th April 2022) - Ghieh, F; Barbotin, A L; Swierkowski-Blanchard, N; Leroy, C; Fortemps, J; Gerault, C; Hue, C; Mambu Mambueni, H; Jaillard, S; Albert, M; Bailly, M; Izard, V; et al.
Abstract: STUDY QUESTION: Could whole-exome sequencing (WES) be useful in clinical practice for men with maturation arrest (MA) after a first testicular sperm extraction (TESE)? SUMMARY ANSWER: WES in combination with TESE yields substantial additional information and may potentially be added as a test to predict a negative outcome of a recurrent TESE in patients with MA. WHAT IS KNOWN ALREADY: At present, the only definitive contraindications for TESE in men with non-obstructive azoospermia (NOA) are a 46, XX karyotype and microdeletions in the azoospermia factor a (AZFa) and/or AZFb regions. After a first negative TESE with MA, no test currently exists to predict a negative outcome of a recurrent TESE. STUDY DESIGN, SIZE, DURATION: In a cohort study, we retrospectively included 26 patients with idiopathic NOA caused by complete MA diagnosed after a first TESE. PARTICIPANTS/MATERIALS, SETTING, METHODS: Twenty-six men with MA at the spermatocyte stage in all seminiferous tubules, according to a histopathological analysis performed independently by two expert histologists, and a normal karyotype (i.e. no AZF gene microdeletions on the Y chromosome) were included. Single-nucleotide polymorphism comparative genomic hybridization array and WES were carried out. The results were validated with Sanger sequencing. For all the variants thought to influence spermatogenesis, we used immunohistochemical techniques to analyse the level of the altered protein. MAIN RESULTS AND THE ROLE OF CHANCE: Deleterious homozygous variants were identified in all seven consanguineous patients and in three of the 19 non-consanguineous patients. Compound heterozygous variants were identified in another 5 of the 19 non-consanguineous patients. No recurrent variants were identified. We found new variants in genes known to be involved in azoospermia or MA [including testis expressed 11 ( TEX11 ), meiotic double-stranded break formation protein 1 ( MEI1 ), proteasome 26s subunit, ATPase 3 interacting protein ( PSMC3IP ), synaptonemal complex central element protein 1 ( SYCE1 ) and Fanconi anaemia complementation group M ( FANCM ) and variants in genes not previously linked to human MA (including CCCTC-binding factor like ( CTCFL ), Mov10 like RISC complex RNA helicase 1 ( MOV10L1 ), chromosome 11 open reading frame 80 ( C11ORF80 ) and exonuclease 1 ( EXO1 )]. LARGE SCALE DATA: Data available on request LIMITATIONS, REASONS FOR CAUTION: More data are required before WES screening can be used to avoid recurrent TESE, although screening should be recommended for men with a consanguineous family background. WES is still a complex technology and can generate incidental findings. WIDER IMPLICATIONS OF THE FINDINGS: Our results confirmed the genetic aetiology of MA in most patients: the proportion of individuals with at least one pathologic variant was 50% in the overall study population and 100% in the consanguineous patients. With the exception of MEI1 (compound heterozygous variants of which were identified in two cases), each variant corresponded to a specific gene—confirming the high degree of genetic heterogeneity in men with MA. Our results suggest that WES screening could help to avoid recurrent, futile TESE in men with MA in general and in consanguineous individuals in particular, but these results need to be confirmed in future studies before clinical implementation. STUDY FUNDING/COMPETING INTEREST(S): The study was funded by the Fondation Maladies Rares (Paris, France), Merck (Kenilworth, NJ, USA), IRSF (Montigny le Bretonneux, France) and Agence de la Biomédecine (Saint Denis, France). There are no competing interests. TRIAL REGISTRATION NUMBER: N/A.